2020
DOI: 10.1007/s11524-020-00498-8
|View full text |Cite
|
Sign up to set email alerts
|

Response to the COVID-19 Outbreak in Urban Settings in China

Abstract: The COVID-19 outbreak in China was devastating and spread throughout the country before being contained. Stringent physical distancing recommendations and shelter-in-place were first introduced in the hardest-hit provinces, and by March, these recommendations were uniform throughout the country. In the presence of an evolving and deadly pandemic, we sought to investigate the impact of this pandemic on individual well-being and prevention practices among Chinese urban residents. From March 2-11, 2020, 4607 indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…1). This is consistent to the trend that large cities tend to have a high numbers of COVID-19 cases [23,24].…”
Section: Transition Of the Number Of Ibd Patients With Covid-19 In Japan And Vaccinated Populationsupporting
confidence: 89%
“…1). This is consistent to the trend that large cities tend to have a high numbers of COVID-19 cases [23,24].…”
Section: Transition Of the Number Of Ibd Patients With Covid-19 In Japan And Vaccinated Populationsupporting
confidence: 89%
“…However, all of the above studies were conducted before the COVID-19 outbreak. In addition, although the COVID-19 outbreak had affected both urban and rural areas, the impact of the epidemic was more profound in urban areas because they were closer to the epicenter of the pandemic and had more intensive population movements ( 37 , 38 ). As a result, the closure of public services and the overburdened medical system in this public health emergency also increased the burden on urban family caregivers ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ni et al (2021) discovered that participants with a college-level educational background had a higher rate of anxiety and depression, although the latter had no statistical significance. Generally consistent with our study, and revealed that having completed college was an independent correlate of having anxiety symptoms ( Ni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%